IMPLEMENTASI KEBIJAKAN PROGRAM AKSEPTOR KB PRIA DI KABUPATEN SUMEDANG - deden haria garmana; Lovita Hendrawati; Neng Lina Puspitasari; Osa Nurfitria; Ratnengsih; Siti Anisa Apriliani (JRPA - Journal of Regional Public Administration, 2023)
The Family Planning Program is not a program run solely by the central government. In the current era of decentralization, the authority of the central government regarding family planning programs must be properly decentralized, as stated in article (23) paragraph (1) of Law Number 52 of 2009 concerning Population Development and Family Development which reads, "The government and local governments are obliged to increase access to and quality of information, education, counseling, and contraceptive services.” Men's low participation in the use of contraceptives can be caused by internal and external factors. This study aims to determine the implementation of the male family planning acceptor program policy at the Family Planning Population Control Service, Women's Empowerment and Child Protection, Sumedang Regency, the obstacles encountered and efforts to overcome them. This research was conducted using qualitative methods. Data collection techniques used by observation, interviews, documentation. The data obtained was validated through: Observation persistence, Data Source Triangulation, Reference Adequacy. Research data are processed through techniques: Data reduction, Data Presentation, Conclusion Drawing, which aims to obtain data to support the final results of the study. Determination of the sample/informant in this study was carried out using purposive sampling, namely as many as 5 people. The final results of this study concluded that the implementation of the male family planning acceptor program policy at the Office of Population Control for Family Planning, Women's Empowerment and Child Protection in Sumedang Regency had not been running effectively. This is based on the lack of studies conducted by program organizers on male family planning acceptor candidates.